Facing difficult but unavoidable choices: Donor blood safety and the deferral of men who have sex with men - Pierik, Roland (Bioethics, 2022)
Blood service organizations employ various ways to ensure transfusion blood safety, including the testing of all donations for transfusion-transmissible infections (TTI) and the exclusion of donors who are at increased risk of a recent infection. As some TTIs are more common among men who have sex with men (MSM), many jurisdictions (temporarily) defer the donation of blood by sexually active MSM. This boils down to a categorical exclusion of a large group solely on the basis of their sexual orientation, which is seen as unduly discriminatory and stigmatizing. Blood service organizations in the U.K. and the Netherlands have recently changed their deferral policies for MSM. The problem of the MSM deferral involves a conflict between fundamental rights: the right of MSM to equal treatment and the right to health of the recipients of blood and blood products. We distinguish and discuss three broad alternative options to the current categorical deferral of MSM donations: (1) completely abandoning donor selection on the basis of sexual behavior, (2) individual risk assessment of the sexual activities of each potential donor, and (3) individual risk assessment of the sexual activities of MSM only. The new U.K. policy falls within the second category, and the new Dutch policy is in the third category. We argue that each approach comes with moral costs but that the most reasonable option is different from the policies of both the U.K. and the Netherlands.